FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI KACANG TANAH DI KECAMATAN SEMAU KABUPATEN KUPANG - Deni K.L. Mudin; Paulus Un; Lika Bernadina (Buletin Ilmiah Impas, 2020)
ABSTRACT Peanuts are one of the high economic value commodities in the dry land area. This commodity also contributes to the social life of the dry land area. This research has been conducted in Semau Sub-district, Kupang Regency, with the aim to determine the amount of income, break event point (BEP), R / C ratio, efficiency of capital use and factors that affect the income of peanuts farming, with the number of farmer respondents as many as 92 people , simple randomly selected. Data that has been collected by survey, library and interview methods; analyzed quantitatively-descriptive using regression methods. The results showed that the total average income of peanut farming in the study location was IDR 1,739,895 with a total average income of IDR 3,498,261 and a total average cost of IDR 1,758,366. While the break event point average of production is 147 Kg and the break event point price is IDR. 6.509, while for the total average the R / C ratio is 1.99. With factors that affect income are production (X1), seed costs (X2), and labor costs (X3). From the regression results with the Cobb-Douglass function the coefficient of determination (R2) is 0.822 with the meaning that variations in independent variables such as production, seed costs and labor costs explain the dependent variable namely income (Y) of 82.20% and the rest 17.80 % is explained by variables outside of the variables analyzed. From the results of the F test (diversity test) it was found that the factors X1, X2, and X3 had a significant effect on income at ⍺ 1%, then accept H1 at least one of: βi ≠ 0. Whereas the results of the t test (partial test) obtained that factors significant effect on income, namely production (X1) and labor costs (X2), while the cost of seeds (X3) does not significantly affect income.